Aviation and aircraft finance: an empirical and real assets comparative study - Yu, David (2019)
This thesis comprises three essays in aircraft and aviation finance. The aviation finance space is now a significant industry where new aircraft deliveries worth well in excess of $126 billion are being invested annually in addition to investments in the secondary markets. (Boeing Capital Corporation, 2017). Leasing, especially operating leasing, is a major driver in aircraft pricing and the asset class given it accounts for 43% of all global Airbus and Boeing and McDonnell Douglas aircraft as of 2017 (Ascend, 2017). There are gaps in the literature in the understandings of the driving factors determining aircraft pricing and leasing especially where it relates to characteristics of the global market and its market segments. Chapter 3 discusses the dynamics and drivers of the aviation finance and leasing landscape both in respects to the global aircraft market and more specifically the China market. In addition, an analysis of the drivers affecting cross border mergers and acquisitions in the industry is developed. Chapter 4 focuses on the empirical data and the market characteristics of aircraft asset pricing over a 21 year period from 1996 to 2017 and time sub-segments to analyze the effects of the great financial crisis. This hand collected large dataset includes a time series of specific aircraft type valuation data from a collection of major aircraft appraisers representing the large commercial aircraft asset class. The aviation asset class also segmented into five different major aircraft type groupings with different weighting construction effects. This chapter fills in the gap in the academic literature by examining empirical analysis and looks into the economic shocks through aviation asset pricing. The main finding suggests that the aircraft asset class has higher value depreciation compared to accounting depreciation and standard deviation is less than 3% throughout the four time segments. After the establishment of the aircraft asset class and the market segmentations, further comparative analyses are conducted in Chapter 5 to deduce the implications to the other 20 real asset classes and major investable benchmarks. This extends the academic conversation by expanding on empirical portfolio theory and the effects economic shocks. In addition to return, correlation, and covariance testing, regression and significance testing are conducted. The data suggests that while the aircraft asset class does not have lower standard deviation and variance but has a lower relative volatility in terms of beta, covariance and correlation over the time periods compared with the comparative sets. The data also suggests that public aircraft lessors have higher excess returns to the relative benchmarks compared to the aircraft asset class in most of the time segments except during the great financial crisis. The regression model results support the conclusions earlier that there is very little explanatory power of the comparative asset classes for the aircraft asset class and its sub-segments with very few independent variables significant at the 5% level.